HCI International 2016 - Posters' Extended Abstracts 18th International Conference, HCI International 2016, Toronto, Canada, July 17-22, 2016, Proceedings, Part I - Stephanidis, Constantine (Communications in Computer and Information Science,, 2016)
This is the first volume of the two-volume set (CCIS 617 and CCIS 618) that contains extended abstracts of the posters presented during the 18th International Conference on Human-Computer Interaction, HCII 2016, held in Toronto, Canada, in July 2016. The total of 1287 papers and 186 posters presented at the HCII 2016 conferences was carefully reviewed and selected from 4354 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers thoroughly cover the entire field of Human-Computer Interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. The papers included in this volume are organized in the following topical sections: design thinking, education and expertise; design and evaluation methods, techniques and tools; cognitive issues in HCI; information presentation and visualization; interaction design; design for older users; usable security and privacy; human modeling and ergonomics.